Administrative Transparency in Libya's Ministry of Health from An Islamic Perspective: Challenges and Determinants - Henaish, Abdulhamid Mesbah; Lubis, Asmuliadi; Wahab, Mohd Abdul (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The issue with the research is that it attempts to examine the administrative openness of the Libyan Ministry of Health from an Islamic point of view. The purpose of this research is to determine, from an Islamic point of view, how transparent the administrative processes of the Libyan Ministry of Health are. The objective also is to determine the factors that contribute to administrative openness as well as the obstacles that stand in the way of administrative transparency. The technique that was used in this research was an analytical descriptive one, and it was aimed at describing and analysing the administrative transparency of the Libyan Ministry of Health from an Islamic view. The findings demonstrated that the Islamic viewpoint of administrative openness centered on honesty and the practical application of the principles of honesty and integrity for the purpose of appeasing Allah. According to the findings of the research, established norms of administrative openness should be rapidly agreed upon and implemented in all institutions under the jurisdiction of the Libyan government. ِ The implications of study indicates the Islamic perspective of administrative transparency on the ministry of health in Libya.